Formulasi dan Uji Mutu Fisik Sediaan Lip Balm Ekstrak Umbi Bit (Beta vulgaris L.) - Tiarini, Diah Galuh; Suradnyana, I Gede Made; Juliadi, Debby (Usadha, 2024)
Dry and chapped lips are one of the problems often faced by some people that will cause pain and discomfort. Lip balm is made from the main ingredient oil or fat that will provide moisture to the lips. The addition of color to lip balm preparations will add its own attractiveness, especially for women, because occasionally it can help improve facial aesthetics. Beetroot (Beta vulgaris L.) It is one of the plants that contains betacyanin pigment which has the potential as a natural dye and has very strong antioxidant activity. The purpose of this study was to determine whether there was a difference in the physical quality of lip balm preparations with variations in beetroot extract (Beta vulgaris L). This research is a laboratory study by formulating beetroot ethanol extract into lip balm preparations in 3 formulas with variations in extract concentration, namely formula I (6%), formula II (10%), and formula III (14%). Physical quality tests of the preparations observed are organoleptis, homogeneity, adhesion, and dispersion. Analysis of organoleptical data and homogeneity was carried out descriptively while the results of adhesion and dispersion tests were analyzed with inferential statistics using IBM SPSS statistics 26 at a 95% confidence level with the One-Way ANOVA test. The results of this study showed that there were differences in the physical quality of beetroot extract lip balm (Beta vulgaris L.) at a FI (6%) with a FII (10%) and FIII (14%) especially in the dosage color, adhesion, and spreadability.